The Role of Work Motivation on Employee Performance at Patimban International Port - Yusman, Fajar Nugraha (Yayasan Pendidikan Belajar Berdikari, 2024)
The purpose of this study is to determine and examine how work motivation influences employee performance in relation to workload. An associative strategy is used in this study, which is a type of research where the relationship or influence between independent and dependent variables is investigated. The 57 employees in this study comprised both the population and the sample. A questionnaire was the method of data collecting employed in this investigation. Partial Least Square-Structural Enquiry (PLS-SEM) is the data analysis method that is employed. Software called Partial Least Square (PLS) is used in this study's data processing. The study's findings show that work motivation can minimise the impact of workload on employee performance and that workload has a major impact on employee performance